Intruder Alert System with Firebase Cloud for Syndicate Store and Service - Badderol, Muhammad Haziq`; Abdullah, Nurul Azma (Applied Information Technology And Computer Science, 2025)
The alert system is key for protecting the privacy and safety of any workplace. Syndicate Store and Service Sdn Bhd currently uses an outdated alert system, which lacks real-time notification capabilities and poses significant security vulnerabilities. Therefore, the proposed system is developed to a modern alert system integrated with Firebase Cloud. This new system aims to enhance security by providing real-time notifications, thus significantly improving the efficiency and reliability of the alert mechanism in the workplace. This system integrates various functionalities such as real-time alert notifications and user monitoring by utilizing a web application, Firebase Realtime Database, and Arduino Uno Wi-Fi Rev2. The development of this proposed system follows the prototype methodology, which involves iterative cycles of requirement gathering, design, build prototype, user evaluation, refine prototype and maintenance. The proposed system is anticipated to reduce security vulnerabilities by providing real-time notifications, allowing for prompt responses to unauthorized access attempts. Additionally, the user-friendly interface and automated processes are expected to streamline the management of users and access control.